Pengaruh Penggunaan Media Pembelajaran Wordwall Terhadap Hasil Belajar PPKn Kelas III SDIT Qurrata Aini Baitussalam Bogor - Fitria Erlinda Panatari Rahman; Salati Asmahasanah; Kosim , Ahmad Mulyadi (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to determine the effect of using Wordwall learning media on the Civic Education (PPKn) learning outcomes of third-grade students. This research employed a quasi-experimental method with a Nonequivalent Control Group Design. The sampling technique used was purposive sampling, involving 64 students from SDIT Qurrata Aini Baitussalam Bogor in the 2024/2025 academic year, consisting of 32 students from Class III Taqwa as the experimental group and 32 students from Class III Sholih as the control group. The data were collected using objective test questions administered as pretests and posttests to measure students’ learning outcomes in Civic Education. The results showed a significant increase in the learning outcomes of students in the experimental class after being taught using Wordwall media, with an average posttest score of 85.03, compared to the control class, which had an average posttest score of 76.25. The improvement between the pretest and posttest scores in the experimental group was 16.00 points, while the control group only showed an increase of 7.719 points. The statistical test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference between the learning outcomes of students taught using Wordwall media and those taught using conventional methods. Therefore, it can be concluded that the use of Wordwall media has a significant effect on improving students' learning outcomes in Civic Education